2017
DOI: 10.3892/mmr.2017.6724
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-448 improves isoflurane-induced learning and memory impairment in rats

Abstract: The present study aimed to investigate the potential role of microRNA‑448 (miR‑448) in isoflurane-induced learning and memory impairment in rats. Sprague‑Dawley rats were used for the construction of isoflurane‑treated models. The Morris water maze test was used to evaluate the effects of isoflurane on rats regarding the following para-meters: Swimming speed, escape latency and time in original quadrant. Influences of isoflurane on neuron apoptosis and miR‑448 expression in rat hippocampus tissue were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Notably, the involvement of miRNAs in anestheticinduced neuron injury has been proposed in recent researches. A study in isoflurane-treated rats reported that miR-448 knockdown suppressed neuron apoptosis, and further participated in the regulation of isofluraneinduced learning and memory impairment [13]. Another study about sevoflurane-induced cognitive dysfunction revealed that the addition of miR-96 promoted cell apoptosis induced by sevoflurane and exacerbated the cognitive function impairment of the rats [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the involvement of miRNAs in anestheticinduced neuron injury has been proposed in recent researches. A study in isoflurane-treated rats reported that miR-448 knockdown suppressed neuron apoptosis, and further participated in the regulation of isofluraneinduced learning and memory impairment [13]. Another study about sevoflurane-induced cognitive dysfunction revealed that the addition of miR-96 promoted cell apoptosis induced by sevoflurane and exacerbated the cognitive function impairment of the rats [14].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, miRNAs have shown potential effect for the management of neurological diseases, including neuron injury induced by anesthesia [10][11][12]. For example, Wu et al have suggested that downregulation of miR-448 plays an important role in improving isoflurane-induced learning and memory impairment through regulating neuron apoptosis [13]. Another study in neonatal rats has also reported that the application of sevoflurane elevates the level of miR-96, which promotes hippocampal neuron apoptosis and weakens the learning and memory performance of the rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-124 promoted cell proliferation and inhibited cell apoptosis of hippocampal neurons via regulation of early growth response 1, thus improving spatial learning and memory ability damaged by isoflurane (Yang et al, 2019). Decrease of miR-448 attenuated learning and memory impairment induced by isoflurane (Wu et al, 2017). However, whether miRNAs are associated with isoflurane-related cognitive dysregulation in diabetes has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anesthetics have certain effects on the expression level of miRNAs in the brain (Lu et al, 2015). Further studies have shown the correlation between the expression of several miRNAs and isoflurane-related cognitive disorders, such as miRNA-153 (Shao et al, 2019), miR-124 (Yang et al, 2019) and miR-488 (Wu et al, 2017). MiR-153 protected against neurotoxicity induced by isoflurane via inhibition of neurocyte apoptosis and promotion of cell proliferation (Shao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we induced isoflurane exposure (for 6 hr) models in neonatal SD rats aged 7 days. Recent studies have highlighted the regulatory roles of microRNAs (miRNAs) in neuron apoptosis and cognitive dysfunction triggered by anesthesia, including isoflurane (Li, Li, Zhuang, & Li, ; Wang, Ding, Lai, Liu, & Shuai, ; Wang, Zheng, Wu, & Niu, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%